Sensitive determination of metronidazole based on Graphene-TiO2 modified glassy carbon electrode in human serum and urine samples - Sehatnia, Baharak; Sabzi, Reza Emamali; Kheiri, Farshad; Nikoo, Abbas (European Journal of Chemistry, 2015)
In the present work, a new Graphene-TiO2 (GR-TiO2) modified glassy carbon electrode (GCE) is suggested for sensitive electrochemical determination of metronidazole (MTZ). Electrochemical studies revealed that GR-TiO2 nanoparticles increased the efficiency of electron transfer kinetics by increasing the available surface area of the electrode and charge mobility between MTZ and GR-TiO2 modified electrode. Compared to bare GCE, the modified electrode greatly enhanced the reduction signal of MTZ. The electrochemical behaviour of the modified electrode and the electrochemical reduction of MTZ were investigated with electrochemical impedance spectroscopy, cyclic voltammetry and differential pulse voltammetry techniques. The charge transfer coefficient (α) was calculated to be 0.694. Under optimized conditions, the linear concentration range and detection limit of MTZ were 5.0×10-7 to 2.5×10-5 M-1 and 5.4×10-8 (S/N = 3), respectively. Finally, this sensing method was successfully applied for the determination of MTZ in human blood serum and urine samples.